Menerapkan Konsep Pelayan Tuhan Perjanjian Baru pada Masa Kini - Asih Rachmani Endang Sumiwi; Joseph Christ Santo (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2019)
The term "servant of God" has a growing meaning, and at this time the phrase has several meanings. In its development there is also the meaning of "servant of God" which shifts from the original understanding. This can cause inconsistencies in the function of God's servant in the congregation. With word studies, this research tries to reformulate the concept of servant of God based on the use of some words about servants in the books of the New Testament. The use of these words in the cultural context at that time showed the characteristics of "servants", and from those characteristics it could be formulated the concept of servants of the Lord's New Testament. The results of this study indicated several criteria that must be owned by a member of the congregation so that he deserves to be set as a servant of God. AbstrakIstilah “pelayan Tuhan” memiliki makna yang berkembang, dan pada saat ini frasa tersebut memiliki beberapa makna. Dalam perkembangannya ada juga makna “pelayan Tuhan” yang bergeser dari pengertian semula. Hal ini bisa menimbulkan inkonsistensi fungsi pelayan Tuhan dalam jemaat. Dengan studi kata, penelitian ini mencoba merumuskan kembali konsep pelayan Tuhan berdasarkan penggunaan beberapa kata tentang pelayan di dalam kitab-kitab Perjanjian Baru. Penggunaan kata-kata tersebut dalam konteks budaya pada waktu itu menunjukkan karakteristik “pelayan”, dan dari karakterisik itu dapat dirumuskan konsep pelayan Tuhan Perjanjian Baru. Hasil dari penelitian ini menunjukkan beberapa kriteria yang perlu dimiliki seorang warga jemaat agar ia layak ditetapkan sebagai pelayan Tuhan.